Multiple endotracheal metastases of combined small cell lung carcinoma. Issue 7 (9th June 2022) - Sugino, Keishi; Ono, Hirotaka; Ando, Masahiro; Kobayashi, Miho; Igarashi, Seiji; Tsuboi, Eiyasu
Key message: We report a very rare case of combined small cell lung carcinoma (C‐SCLC) which presented as persistent cough and was due to endotracheal metastases. Clinicians should be aware of this unusual site of metastases from a C‐SCLC. Abstract : We report a very rare case of combined small cell lung carcinoma (C‐SCLC) which presented as persistent cough and was due to endotracheal metastases. Clinicians should be aware of this unusual site of metastases from a C‐SCLC as recognition and treatment improved our patient condition.